APPLIED IR TRAINING AND AN EFFECTIVE FOREIGN POLICY - A. A. Baykov (Vestnik MGIMO-Universiteta)
This article examines the main aspects of the IR experts' professional education and training, aimed at improving the efficiency of the foreign office staff. A new approach has been taken to the problem of updating and rationalization of the current academic programs (especially, MA training programs) in order to boost the competitiveness of national educational system at the global education market. The main focus is shifted from marketing to quality and "content" characteristics of the professional training in IR studies' area within the organization of higher education. The author draws on the empirical data, collected by means of analysis, processing and generalization of expert assessments and evaluations of Russian and foreign participants of international faculty and university forums in International Studies in 2015. As a result, the article proposes an ideal model of the master's program, developed by the author, based on "benchmark"International Relations/World Politics programs, which are highly valuated by the respondents. Moreover, it examines the most relevant issues, concerning the framework of students' teaching process (including preparation of master's theses), further employment of graduates and, finally, the development/modernisation of teaching staff. In conclusion, the article highlights recommendations on probable reforms of higher education in IR studies' area. The author does not criticize the national education system destructively. On the contrary, the inevitable question is how to converge the best qualities of domestic and foreign institutions of higher education system in a harmonious way. The article is designed and might be of interest for higher education and training experts, as well as for a wide range of readers interested in the education and training of the foreign office staff.